“Hanging out” with judicial and legal elites: Reflections on researching “up” - Kisakye, Diana (Institute of African Studies, 2023)
The challenges of researching “up” are widely acknowledged. Moreover, these hurdles are intensified for law and courts field investigators where the profession’s cherished virtues – protocol, hierarchy and decorum – hamper access to interviewees and could potentially be detrimental to rapport building for the researcher unfamiliar with courtroom formality. This paper draws on the author’s field experience to highlight the potential of the informal dimension of fieldwork – “hanging out” – in traversing some of the limits of researching legal and judicial elites. It teases out the complexities of studying judges as political actors and the peculiar circumstances of studying legal elites in close-knit circles. Through “hanging out” at relevant court events, strategically positioning oneself in social events and informally building rapport, the author gained access to spaces usually closed off to outsiders. By “hanging out” with judges, the author challenged her perceptions of absolute judicial fidelity to the law, interrogated their professed devotion to apoliticism and the experience humanised judges and helped her deal with her own discomfort with interviewing judges. The paper concludes by weighing the promises and limits of the informal approach to researching legal and judicial elites, pondering ethical considerations, the researcher’s positionality and the boundaries of continuous residence.
Keywords: Researching courts; hanging out; judicial research; Informality; African sub-regional courts